THE FOREIGN INVESTMENT IN THE INDONESIAN CAPITAL CITY FROM THE PERSPECTIVE OF THE CONSTITUTIONAL ECONOMIC CONCEPT IN INDONESIA - EKI SUDARNO; Zulfikri Toguan; Rafael Febriant Tua Hutauruk (Yayasan Pendidikan Islam Almatani, 2026)
Abstract Development must continue to be carried out in order to create equity, the development carried out today aims to sustain life in the present and the future. If we feel the impact of development today, it means that our predecessors managed the country successfully. And all that is done today is for the good of the world. This study is a research literature. Activities are carried out systematically to collect, process, and conclude data using certain methods/techniques to find answers to the problems faced. This study uses a qualitative approach, a research process to understand human or social phenomena by creating a comprehensive and complex picture that can be presented in words, reporting detailed views obtained from source informants, and carried out in a natural setting. The data of this study were obtained from library sources consisting of books, journals, Scientific Papers, legislation, documents, and so forth. The results showed that the transfer of the state capital missed the complete process and mechanism, seen the most dominant executive in the process of moving the capital. The transfer, which was established in conjunction with the covid-19 response, caused a negative reaction from the public. Then the investment mechanism carried out by the government is considered contrary to the constitutional economic system because the government ignores the interests of the people. Keywords: Foreign Investment, IKN, economic Constitution.